Autophagy inhibition enhances anti‐pituitary adenoma effect of tetrandrine. (26th May 2021) - Lyu, Liang; Hu, Yu; Yin, Senlin; Wang, Li; Ye, Feng; Wang, Mengmeng; Zhou, Yueling; Ma, Weichao; Chen, Cheng; Jiang, Yong; Wang, Zeming; Jiang, Shu; et al.
Abstract : Pituitary adenoma (PA) is a benign intracranial neoplasm originated from pituitary gland. Surgery is the first‐line therapy for most of PAs, but lead to unsatisfactory prognosis in some cases. Tetrandrine (Tet) has anticancer effect on some cancers. However, growth inhibition effect on PA is unknown. To elucidate the inhibitory effect of Tet on the growth of PA and its potential mechanisms, we validated the in vitro and in vivo anti‐PA effect of Tet and illustrated the cellular and molecular alterations by confocal microscopy observation, flow cytometry, and RNA interference. Tet inhibited PA cell growth in vitro and tumor progression in vivo. Tet induced autophagy and apoptosis in a dose‐dependent manner. Low dosage (1.25 μM) of Tet induced PA cell autophagy by down‐regulation of MAPK/STAT3 signal. While, higher dosage (5.0 μM) of Tet partially induced PA cell death through caspase‐dependent apoptosis. Autophagy inhibitors enhanced Tet‐induced caspase activity and apoptotic cell death. These findings demonstrated that Tet has anti‐PA effect by inducing autophagy and apoptosis through MAPK/STAT3 signaling pathway attenuation and autophagy inhibition might enhance its anti‐PA effect, indicating that Tet (or combined with autophagy inhibitor) is a potential therapeutic regimen for PAs.